2010
DOI: 10.1371/journal.pone.0010971
|View full text |Cite|
|
Sign up to set email alerts
|

Fungi Unearthed: Transcripts Encoding Lignocellulolytic and Chitinolytic Enzymes in Forest Soil

Abstract: BackgroundFungi are the main organisms responsible for the degradation of biopolymers such as lignin, cellulose, hemicellulose, and chitin in forest ecosystems. Soil surveys largely target fungal diversity, paying less attention to fungal activity.Methodology/Principal FindingsHere we have focused on the organic horizon of a hardwood forest dominated by sugar maple that spreads widely across Eastern North America. The sampling site included three plots receiving normal atmospheric nitrogen deposition and three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(63 citation statements)
references
References 51 publications
3
60
0
Order By: Relevance
“…These approaches have been combined in studies that specifically target laccase (Luis et al, 2005a), exocellulase Eichorst and Kuske, 2012), or a range of various glycosyl hydrolases and oxidases (Kellner and Vandenbol, 2010) in forest soils and are highly attractive due to their theoretical potential to assign gene sequences to specific groups of soil microorganisms. Single-gene-oriented surveys suffer from limitations, however, due to their limited applicability to only highly similar gene sequences (often a single protein family) and varying specificity of polymerase chain reaction (PCR) primers.…”
Section: Challenges For Current Research In Microbial Decompositionmentioning
confidence: 99%
“…These approaches have been combined in studies that specifically target laccase (Luis et al, 2005a), exocellulase Eichorst and Kuske, 2012), or a range of various glycosyl hydrolases and oxidases (Kellner and Vandenbol, 2010) in forest soils and are highly attractive due to their theoretical potential to assign gene sequences to specific groups of soil microorganisms. Single-gene-oriented surveys suffer from limitations, however, due to their limited applicability to only highly similar gene sequences (often a single protein family) and varying specificity of polymerase chain reaction (PCR) primers.…”
Section: Challenges For Current Research In Microbial Decompositionmentioning
confidence: 99%
“…Degradation studies are mainly biotic, aerobic, and co-metabolic. Studies have shown that certain bacteria [10] and fungi [11] are able to break down various biopolymers in soil. Lignocellulosic biomass degradation has been widely studied in wood-rotting Baciomycetes fungi due to their potential to degrade lignin.…”
Section: Introductionmentioning
confidence: 99%
“…Lignin decay is mediated by lignin-peroxidases (LiP), manganese-peroxidases (MnP), and laccases thought to be of largely fungal origin and can result in complete metabolism to CO 2 (26)(27)(28). The high redox potential of LiP and MnP enables the oxidation of both phenolic and nonphenolic lignin units (ϳ90% of the polymer), whereas the lower redox potential of laccases oxidize phenolic lignin units, often comprising ϳ10% of the polymer (29).…”
mentioning
confidence: 99%